2008
DOI: 10.1007/s10822-008-9186-7
|View full text |Cite
|
Sign up to set email alerts
|

Docking and multivariate methods to explore HIV-1 drug-resistance: a comparative analysis

Abstract: In this paper we describe a comparative analysis between multivariate and docking methods in the study of the drug resistance to the reverse transcriptase and the protease inhibitors. In our early papers we developed a simple but efficient method to evaluate the features of compounds that are less likely to trigger resistance or are effective against mutant HIV strains, using the multivariate statistical procedures PCA and DA. In the attempt to create a more solid background for the prediction of susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Lys103Asn is reported in literature as the most common mutation observed during therapy with first generation NNRTIs as if increases the stability of the closed form of the hydrophobic pocket [14,27,30,31,32,33]. Interestingly, this replacement did not seem to influence interactions between THD and most mutants (RT-1, RT-5, RT-6, RT-8, RT-9, RT-10 and RT-11) with the exception of RT-6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lys103Asn is reported in literature as the most common mutation observed during therapy with first generation NNRTIs as if increases the stability of the closed form of the hydrophobic pocket [14,27,30,31,32,33]. Interestingly, this replacement did not seem to influence interactions between THD and most mutants (RT-1, RT-5, RT-6, RT-8, RT-9, RT-10 and RT-11) with the exception of RT-6.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the importance of Lys101 on the orientation of NNRTIs in the binding pocket, and the existence of a mutation at this position in HIV-1 infected patients, we performed a molecular docking in the enzyme presenting the Lys101Glu mutation, the most common according to the literature [32] (Figure 4). The evaluation of the best docking pose showed that the hydrogen bond with the residue of position 101 is maintained in the presence of mutation probably because the hydrogen bond occurs between the hydroxyl of THD and the carbonyl oxygen of the residue backbone.…”
Section: Resultsmentioning
confidence: 99%
“…The development of the commercially available inhibitors, such as: saquinavir (ROCHE); lopinavir; ritonavir and tipranavir; are based on such structural analysis, occasionally combined with quantum theoretical methods [211,212]. The HIV protease database contains structures of the HIV protease and their complexes with inhibitors, together with analysis tools and information about AIDS: http://mcl1.ncifcrf.gov/hivdb/.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…The molecular docking and molecular dynamics (MD) simulation were often used to understand the binding conformations of ligands in the active sites of HIV-1-related proteins. Furthermore, a comparative analysis with the combination of docking and multivariate methods was used to study the drug resistance of HIV-1 inhibitors and to further design new compounds with appropriate structural features (Almerico et al, 2008). To further explore the essential structural and pharmacological features of the novel DHPYs as HIV-1 NNRTIs in this study, the combination of 3D-QSAR models, molecular docking, and MD simulation was applied to analyze the 3D-QSARs of these DHPYs and their binding modes in the HIV-1 RT.…”
Section: Introductionmentioning
confidence: 99%